Peningkatan nilai tambah ulat sagu dan mujair asap melalui inovasi pengolahan higienis dan pemberdayaan masyarakat di Kampung Yoboi, Papua - Tingginehe, Rosmin Mariati; Pariaribo, Konstantina (Politeknik Kesehatan Kemenkes Aceh, 2025)
Yoboi Village, Sentani, Papua, has the potential for local food resources, including sago caterpillars and tilapia. These commodities are important sources of animal protein and play a strategic role in supporting food security among Papuan communities; however, their utilization has been limited to household consumption, often using simple techniques without adherence to hygiene standards, packaging, or labeling. This community service program aimed to improve community capacity in hygienic processing, vacuum packaging, labeling, and marketing of smoked sago caterpillars and tilapia products. The method applied was a community-based participatory action research approach, covering needs assessment, module development, structured training, hands-on practice, and rapid reflection. A total of 60 participants were involved, representing fishermen, sago caterpillar collectors, homemakers, and youth. Evaluation was conducted through observation, station checklists, and pre- and post–knowledge tests. The results showed a significant increase in knowledge, with the proportion of participants having high knowledge rising from 11,6% to 71,7% after the training (p = 0,023). Sample products of smoked sago caterpillars and smoked tilapia were successfully produced with vacuum packaging and minimal labeling, showing more consistent quality and longer shelf life. Participants also agreed to establish a community group/MSME and initiate early marketing strategies, both online and offline. This program, as a participatory training, strengthened both the community’s technical skills and institutional readiness.